Artificial Intelligence Applications to Smart City and Smart Enterprise - Impedovo, Donato; PIRLO, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Smart cities operate under more resource-efficient management and economy than ordinary cities. As such, advanced business models have emerged around smart cities, which led to the creation of smart enterprises and organizations that depend on advanced technologies. This book includes 21 selected and peer-reviewed articles contributed in the wide spectrum of artificial intelligence applications to smart cities. Chapters refer to the following areas of interest: vehicular traffic prediction, social big data analysis, smart city management, driving and routing, localization, safety, health, and life quality.